Synthesis Centre for Research and Education - (:unkn) unknown (My University, 2026)
Associate member Synthesis Centre for Research and Education, a pioneering enterprise implementing projects with a social impact, particularly in the fields of entrepreneurship, migrant integration and social inclusion (www.synthesis-center.org/team).